2013
DOI: 10.1016/j.bmc.2013.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of 6,7-methylenedioxy-4-substituted phenylquinolin-2(1H)-one derivatives as novel anticancer agents that induce apoptosis with cell cycle arrest at G2/M phase

Abstract: Novel 6,7-methylenedioxy-4-substituted phenylquinolin-2-one derivatives 12a–n were designed and prepared through an intramolecular cyclization reaction and evaluated for in vitro anticancer activity. Among the synthesized compounds, 6,7-methylenedioxy-4-(2,4-dimethoxyphenyl)quinolin-2(1H)-one (12e) displayed potent cytotoxicity against several different tumor cell lines at a sub-micromolar level. Furthermore, results of fluorescence-activated cell sorting (FACS) analysis suggested that 12e induced cell cycle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Among them, 11e exhibited the highest potencies against these four tumour cell lines with IC 50 values of 0.014, 0.035, 0.04 and 0.028 μM respectively. Notably, compound 11e exhibited improved cytotoxicity in comparison with 6,7‐methylenedioxy‐4‐(2,4‐dimethoxyphenyl)quinolin‐2(1 H )‐one, the most potent 4‐PQ analog previously reported (IC 50 0.4, 1.0, 0.9 and 7.4 μM against the four tumour cell lines) (Chen et al ., ). SAR study on these new compounds revealed that a 3′,5′‐dimethoxybenzyloxy moiety, linked at the 4‐position of a 6‐methoxy‐2‐quinolone backbone is most favourable for increased antiproliferative activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 11e exhibited the highest potencies against these four tumour cell lines with IC 50 values of 0.014, 0.035, 0.04 and 0.028 μM respectively. Notably, compound 11e exhibited improved cytotoxicity in comparison with 6,7‐methylenedioxy‐4‐(2,4‐dimethoxyphenyl)quinolin‐2(1 H )‐one, the most potent 4‐PQ analog previously reported (IC 50 0.4, 1.0, 0.9 and 7.4 μM against the four tumour cell lines) (Chen et al ., ). SAR study on these new compounds revealed that a 3′,5′‐dimethoxybenzyloxy moiety, linked at the 4‐position of a 6‐methoxy‐2‐quinolone backbone is most favourable for increased antiproliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is well known as a process of programmed cell death (Elmore, 2007). In our previous study, 4-phenyl-2-quinolone analogues (4-PQs) induced cell cycle arrest and apoptosis in both HL-60 and H460 cells (Chen et al, 2013b). In order to characterize the cellular basis for the antiproliferative effects of the selected derivative 11e, we investigated the ability of this compound to induce apoptosis in COLO 205 cells.…”
Section: Morphological Changes and Apoptosis In Colo 205 Cells Inducementioning
confidence: 99%
See 1 more Smart Citation
“…The Hoechst 33258 staining assays were conducted according to our previous report [33]. The COLO 205 cells were plated at a density of 2.5×10 5 cells per well in 12-well plates, and then incubated with 0.5 μM of compound 11 for 12 h to 48 h. Cells were directly examined and photographed under a contrast-phase microscope.…”
Section: Methodsmentioning
confidence: 99%
“…More conventional prodrug approaches implying the formation of sodium phosphates on phenolic hydroxyl groups have also been attempted. [214] Modification of the basic flavone pharmacophore by translation of the 2-phenyl ring, such as in the 4-phenylquinolin-2(1H)-ones, leads to aza-podophyllotoxin analogues with much less potent cytotoxic activity, [217] but elongation of the linker to the quinoline has resulted again in nanomolar cytotoxic compounds. [218] Structurally related acridones with pendant phenethyl substituent have also been shown to be potent TPI, an activity which is not accompanied by potent cytotoxicity against cancer cells in vitro.…”
Section: Quinolones and Acridonesmentioning
confidence: 99%